Receptor Guanylyl Cyclases in Sensory Processing - Maruyama, Ichiro N. (Frontiers in Endocrinology, 2017)
Invertebrate models have generated many new insights into transmembrane signaling by cell surface receptors. This review focuses on receptor guanylyl cyclases (rGCs) and describes recent advances in understanding their roles in sensory processing in the nematode, Caenorhabditis elegans. A complete analysis of the C. elegans genome elucidated 27 rGCs, an unusually large number compared with mammalian genomes, which encode seven rGCs. Most C. elegans rGCs are expressed in sensory neurons, and play roles in sensory processing, including gustation, thermosensation, olfaction, and phototransduction, among others. Recent studies have found that by producing a second messenger, guanosine 3’,5’-cyclic monophosphate (cGMP), some rGCs act as direct sensor molecules for ions and temperatures, while others relay signals from G-protein coupled receptors (GPCRs). Interestingly, genetic and biochemical analyses of rGCs provide the first example of an obligate heterodimeric rGC. Based on recent structural studies of rGCs in mammals and other organisms, molecular mechanisms underlying activation of rGCs are also discussed in this review.